Trafika Europe : essential new European literature - Singer, Andrew (The Pennsylvania State University Press, 2016)
"A collection of fiction and poetry representing the literature of cultures across Europe, including Shetland Scots, Occitan, Latvian, Polish, Armenian, Italian, Hungarian, German, Slovenian, Faroese and Icelandic"--Provided by publisher